TEACHER’S VOCATION AND STUDENTS’ ATTITUDES TOWARDS A CHOICE OF TEACHER’S VOCATION - Zariņa, Sandra; Drelinga, Elga; Iliško, Dzintra; Krastiņa, Elfrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Research published by Eurydice in 2015„Teaching Profession in Europe: Practices, Perceptions, and Policies” indicates to the significance of teaching vocation in a sustainability-oriented learning environment, but at the same time there is an indication of a low prestige of teaching vocation in Latvia. The situation in Latvia reveals a significant problem teacher trainers need to deal with. There are very high standards set for teachers’ profession, on the other side, the politics of the country is oriented towards a motivation of young specialists to choose teacher’s vocation. In order to train competent teachers this is essential to explore a motivation of learners to acquire teaching profession and to make a decision to work at school and in the kindergarten. The aim of this study is to explore reasons why youth in Latvia choose to study in the educational programs and to explore changes in students’ attitudes during their learning process in teacher training institutions.